REDUCE ENERGY CONSUMPTION BY ADJUSTING THE ELECTRODVIGATE SPEED OF THE LINTER DEVICE: This article discusses cotton fiber, obtaining secondary products from chickens, ageing the plumbing industry, machine electrodvigates used in the cotton industry, and their use. It also mentions the experience of European countries in the lintering technologies used in plumbing companies and the cultivation of cotton in foreign countries. - Shamshitdinov, Maqsudbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
You can increase the control token (Ib) given to the control churn and reduce the working churn voltage (Uin) and increase the load voltage (U). The variable token bridge is corrected in a semiconductor fixer with a schematic and transmitted to the engine yacht. Therefore, by changing the value of the land in the control churn, you can adjust the corrected voltage given to the “yakor”, resulting in the speed of the engine. In such a scheme, the biking of the mechanical characteristics of the engine is much lower. There are also magnetic amplifier schemes with a magnetic amplifier with a reverse communication chain, an internal feedback chain, and a reverse communication chain by land and voltage. With a much higher rate in these schemes, it is possible to adjust the speed of various powerless token engines.